2016
DOI: 10.1111/ajd.12548
|View full text |Cite
|
Sign up to set email alerts
|

Survival rates of biological therapies for psoriasis treatment in real‐world clinical practice: A Canadian multicentre retrospective study

Abstract: A progressive decrease in treatment adherence was seen with all four biologics, as expected, but the survival rate of ustekinumab was highest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…8,[10][11][12][13][14] However, the survival rates were lower compared to a recent study by Marinas et al 10 For instance, 2-and 4-year survival rates for UST in our study were 0.74 and 0.60, respectively, compared to 0.856 and 0.755 found by Marinas et al 10 A similar 4-year survival rate was found by Gniadecki et al 8 as well. Reasons for the lower survival rate could include differences in patient characteristics, as the majority of the data from Gniadecki et al 8 and all of the data from Marinas et al 10 were from academic institutions compared to private dermatologic practices in our study. Another reason for lower survival in our cohort may have been the availability of alternative therapies as major clinical trial programs for newer agents were introduced during this period, including 3 IL-17 inhibitors and the oral agents, apremilast and tofacitinib.…”
Section: Discussionsupporting
confidence: 69%
“…8,[10][11][12][13][14] However, the survival rates were lower compared to a recent study by Marinas et al 10 For instance, 2-and 4-year survival rates for UST in our study were 0.74 and 0.60, respectively, compared to 0.856 and 0.755 found by Marinas et al 10 A similar 4-year survival rate was found by Gniadecki et al 8 as well. Reasons for the lower survival rate could include differences in patient characteristics, as the majority of the data from Gniadecki et al 8 and all of the data from Marinas et al 10 were from academic institutions compared to private dermatologic practices in our study. Another reason for lower survival in our cohort may have been the availability of alternative therapies as major clinical trial programs for newer agents were introduced during this period, including 3 IL-17 inhibitors and the oral agents, apremilast and tofacitinib.…”
Section: Discussionsupporting
confidence: 69%
“…The drug survival for each biologic and the status of patients being biologic-naïve or -experienced are shown in Supplementary Table S1 . There were 28 studies 9 36 (13,303 patients) reporting data for etanercept, 32 studies 9 11 , 13 19 , 21 31 , 33 – 43 (12,109 patients) for adalimumab, 20 studies 9 , 11 , 13 19 , 21 24 , 26 , 27 , 29 , 30 , 34 , 35 , 40 (2,613 patients) for infliximab, and 22 studies 9 , 13 , 14 , 16 , 19 , 22 31 , 33 36 , 40 , 44 , 45 (4,606 patients) for ustekinumab.…”
Section: Resultsmentioning
confidence: 99%
“…The largest study was the multicentric study called OSCAR, conducted in Italy between 2007 and 2011, including 650 patients with a mean follow-up of 2.4 years [18]. Another important study was a multicentric Canadian study that enrolled 398 patients from 2005 to 2014 and followed them for an average of 2.5 years [38]. The latter study had information on all 4 biological therapies.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical outcomes (mainly PASI) were reported in 75% of prospective studies [27, 39, 47-53], in about 50% of prospective registries [20, 24, 54-61] and retrospective studies [29, 30, 32, 34, 37, 62-70], and in no retrospective administrative databases/claims. Drug survival of biological therapies was reported in over 60% of prospective registries [14, 20, 21, 24, 25, 31, 54, 57, 71-74], retrospective studies [18, 19, 22, 23, 26, 29, 30, 32, 34, 37, 38, 68, 70, 75-77] and administrative databases/claims [28, 35, 36, 40-42, 46], and less frequently (33%) in prospective studies [27, 33, 52, 78]. Subanalyses on reasons of discontinuation, such as switching, dose augmentation, or biological therapy restarting, were scanty.…”
Section: Resultsmentioning
confidence: 99%